Variação espacial do grau de trofia e da biomassa fitoplanctônica no reservatório de Itupararanga (São Paulo, Brasil) - Taniwaki, Ricardo Hideo [UNESP]; Rosa, André Henrique [UNESP]; Calijuri, Maria do Carmo; Carlos, Viviane Mochini [UNESP] (My University, 2011)
Nowadays the Brazilian reservoirs has suffered great pressure due to increasing demand for water for diverse purposes, being one of the largest eutrophication problems caused by man. The Itupararanga reservoir provides environmental services to more than one million people and is one of the main sources of the Sorocaba River basin and middle Tietê. Thus this study aimed to determine the spatial variability of the trophic level and phytoplankton biomass in the reservoir, as well as the concentrations of nutrients and also check your environment according to CONAMA 357/2005 (BRASIL, 2005). For this, a collection that was conducted in six sampling stations and the measures of pH, conductivity, dissolved oxygen, water temperature, water transparency, total phosphorus, total phosphorus, dissolved nitrite, nitrate, chlorophyll-a and sediment size analysis . The results indicated that there was no spatial variation of the degree of trophy in the Itupararanga reservoir, but there was spatial variation of nutrient concentrations and chlorophyll-a, corroborating theoretical models of reservoir compartmentalization.

Atualmente os reservatórios brasileiros vêm sofrendo grandes pressões devido à crescente demanda por água para diversos fins, sendo a eutrofização uns dos maiores problemas causados pelo homem. O reservatório de Itupararanga fornece serviços ambientais para mais de um milhão de pessoas e é um dos principais manancias da bacia do rio Sorocaba e médio Tietê. Desta forma, o presente trabalho teve como objetivo verificar a variabilidade espacial do grau de trofia e da biomassa fitoplanctônica do reservatório, assim como as concentrações de nutrientes e também verificar seu enquadramento conforme a resolução CONAMA 357/2005 (BRASIL, 2005). Para isto foi realizada uma coleta da água superficial em seis estações amostrais e medidas de pH, condutividade elétrica, oxigênio dissolvido, temperatura da água, transparência da água, fósforo total, fósforo total dissolvido, nitrito, nitrato, concentrações de clorofila-a e no sedimento foi realizada análises granulométricas. Os resultados indicaram que não houve variação espacial do grau de trofia do reservatório de Itupararanga, porém houve variação espacial das concentrações de nutrientes e clorofila-a, corroborando com modelos teóricos de compartimentalização de reservatórios.
Spatial variation of trophic status and phytoplanktonic biomass in itupararanga reservoir (são paulo, brazil)
Keywords: represa de Itupararanga; fitoplâncton; biomassa; Trofia; Nutrientes; CONAMA; Reservoir; Itupararanga; Trophic status; Nutrient; CONAMA